Financial Feasibility of Investing in Smallholder Cow-Calf Cooperatives in Baluran National Park - Mark Rademaker; Any Suryantini; Jangkung Handoyo Mulyo (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2017)
Livestock grazing is a major driver of human-wildlife confl ict in conservation areas. Currently, it is estimated that 3000 heads of cattle illegally grazing within Baluran National Park (BNP) in East Java. The recent research has suggested the potential of livestock system intensifi cation to reduce land-use and conflict through conservation priorities. The research goal was to investigate the fi nancial feasibility of starting intensive cow-calf cooperatives by smallholders in the BNP area. Data were collected using Farm surveys in a Criterion sampling design. Optimal herd management plans were generated using whole farm Linear Programming and fi nancial feasibility was assessed using Discounted cash-flow analysis and debt-servicing capabilities. Investment lifetime was set at 15 years and four alternative varieties of cattle were taken from Bali, Peranakan Ongole, Limousin and Simmental. Results show that investing in all varieties represents a positive investment opportunity. Bali cattle obtaining the highest NPV (53.769), IRR (14,25%) and B/C ratio (1,13). Farmer income can be increased by 163% by combining additional Off-farm labor. However, debt servicing capabilities of cow-calf cooperative activities showed that the loan principal can only be repaid in the 10th year instead of the maximum eight years set by the government cow-calf credit scheme. We urge the government to reconsider either the grace period or the repayment time of the credit scheme to better fit the cash-fl ow characteristics of cow-calf enterprises.